2022
DOI: 10.1111/ppc.13078
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nurses' professional values, empathy, and patience: A descriptive cross‐sectional study

Abstract: Aim The aim of this study was to determine the relationships between the nurses' professional values and their empathy and patience levels, and the factors affecting them. Methods This descriptive cross‐sectional study was conducted with 215 nurses working at a university hospital between February and April 2021. Data were collected using the “Nurse Information Form,” “Nurses' Professional Values Scale,” “Patience Scale,” and “The Toronto Empathy Questionnaire.” Findings Results of our study revealed that nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It was found in this study that the nurses’ PS mean score (39.96 ± 6.05) was high when the highest score obtainable on the scale was evaluated. In similar studies in the literature, nurses’ patience levels were reported to be high (Isik et al, 2022; Süzen and Çevik, 2020). In addition, patience levels were higher in nurses who were aged 29 years or more, who had worked in the ICU or in total for 6 years or more, and who were married and had children ( p < 0.05; Table 3).…”
Section: Discussionmentioning
confidence: 54%
“…It was found in this study that the nurses’ PS mean score (39.96 ± 6.05) was high when the highest score obtainable on the scale was evaluated. In similar studies in the literature, nurses’ patience levels were reported to be high (Isik et al, 2022; Süzen and Çevik, 2020). In addition, patience levels were higher in nurses who were aged 29 years or more, who had worked in the ICU or in total for 6 years or more, and who were married and had children ( p < 0.05; Table 3).…”
Section: Discussionmentioning
confidence: 54%
“…This may be because people with high levels of happiness accumulate more positive emotions, are satisfied with their lives, and can positively influence their organizational performance, which in turn positively affects the quality of care delivery [37]. Moreover, nurses with positive psychological qualities, such as resilience, and empathy, tend to maintain consistent positive expectations about future outcomes, which then leads to more positive outcomes that enhance their mental health, job satisfaction, professional self-concept [38][39][40], and career decision-making [41]. However, individual attributes take longer to develop and may be influenced by the environment, education, and experience [36].…”
Section: Nurses' Mindsets Psychological Qualities and Attitudes As An...mentioning
confidence: 99%
“…26 Like compassion, it too has been a subject of interest since the 19 th century and is included in professional nursing standards and competencies. 27,28 Empathy is also well recognised as an essential facet of nursing care which facilitates therapeutic communication, 20,[28][29][30][31][32][33] improves patient outcomes and satisfaction, 28,29,[33][34][35][36] and is a key element of person-centred care. 32,37,38 Although nursing education frequently refers to compassion and empathy, there is much speculation on whether compassion is an inherent trait, and its teachability.…”
Section: Vignette -Historical Figures Known For Compassionmentioning
confidence: 99%